PENGARUH KONSENTRASI DAN SAAT PEMBERIAN SITOZIM TERHADAP PERTUMBUHAN DAN HASIL KAPAS (Gossypium hirsutum L.) - , Purwono; Sri Lilis Herlianthy (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
Experiment to investigate the effect of concentration and time of application of Sitozim was conducted at greenhouse in Sindangbarang Experimental Station, Bogor Agricultural University, Bogor, from February to July 1993. Four levels concentration (0, 1.25, 2.5, and 3.75 mi/l) and three application time (vegetative, generative, and vegetative+generative stage) were applied. The experimental design was Randomized Block Design with three replications. Vegetative growth was not affected by the treatments. Higher concentration gave higher weight of boll per plant, seed-cotton weight per plant, and fibre weight per plant. However, there were no significant effects of all treatments on fibre quality.